STRATEGI DAN METODA PEMBELAJARAN BIOLOGI BERBASIS IMTAQ DI SEKOLAH/MADRASAH - Milya Sari (Ta'dib, 2010)
Biology, as one field of science, provides various learning experience to understand the concept and the process of science. Biology subject aims at promoting positive attitudes toward Biology by realizing the orderliness and the beauty of the universe and praising the Almighty of God. It is also responsible for establishing Islamic values through instructional materials being taught and consequently the instructional goals can be attained. To arrive at such goals, particular learning approach, strategy, and even method which integrate Islamic values into instructional materials are really needed. This, in turn, will make learning meaningful to students and promote better learning output. Nevertheless, teachers’ readiness, evaluation system and the availability of learning facilities might become the pitfalls.Kata kunci: strategi dan metoda pembelajaran, nilai-nilai imtaq